Do citizens make inferences from political candidate characteristics when aiming for substantive representation?. (February 2019) - Arnesen, Sveinung; Duell, Dominik; Johannesson, Mikael Poul
Abstract: We elicit citizens' preferences over hypothetical candidates by applying conjoint survey experiments within a probability-based online panel of the Norwegian electorate. Our experimental treatments differ in whether citizens receive information about candidates' social characteristics only, candidates' issue positions only, or both. From this, we identify whether citizens are able to infer substantive policy positions from the descriptive characteristics of potential representatives and use that information to make candidate choices that achieve substantive representation. We find that candidate choice is driven more by knowledge about candidates' issue positions than by knowledge about their social characteristics and that citizens value substantive representation more robustly than descriptive representation. Importantly, while the direct experimental test of whether voters use the information they obtain from descriptive markers to choose a candidate that gives them substantive representation is inconclusive, we find that voters form beliefs about candidates' issue positions based solely on candidates' social characteristics.